1995
DOI: 10.1111/j.1442-9993.1995.tb00519.x
|View full text |Cite
|
Sign up to set email alerts
|

Selection of a suitable cladoceran species for toxicity testing in turbid waters

Abstract: Two Australian cladocerans, Moina australiensis Sars and a species oi Ceriodaphnia, were evaluated as possible biological indicator organisms to assess the toxicity of irrigation supply and drainage water of the Murrumbidgee and Coleambally Irrigation Areas, M. australiensis, being large (-2000 /um) and orange, was initially chosen to overcome visibility problems in highly turbid Australian inland waters. However, the organism responded erratically in culture. Mortality was high and neonate production was unpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 2 publications
(4 reference statements)
2
4
0
Order By: Relevance
“…Chem. 19, 2000 93 the Sydney clone exposed in test volumes ranging between 40 and 200 ml and others have reported satisfactory results for tests conducted in 15-ml volumes with the Sydney clone [10][11]. In summary, our results suggest that the Sydney clone can be reliably cultured and tested using the methods described herein, which are based on Environment Canada and U.S. EPA guidelines.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Chem. 19, 2000 93 the Sydney clone exposed in test volumes ranging between 40 and 200 ml and others have reported satisfactory results for tests conducted in 15-ml volumes with the Sydney clone [10][11]. In summary, our results suggest that the Sydney clone can be reliably cultured and tested using the methods described herein, which are based on Environment Canada and U.S. EPA guidelines.…”
Section: Discussionsupporting
confidence: 57%
“…However, they noted that further improvements could be made with respect to diet and water in order to achieve consistently acceptable survival and reproductive performance. Moreover, subsequent studies conducted with this species used a variety of test and culture methods [10][11][12][13]. Consequently, our objective was to further evaluate the effects of container size and volume, diet, and dilution water on the survival and reproduction of the Sydney clone with the goal of validating existing procedures widely used in Canada and the United States.…”
Section: Introductionmentioning
confidence: 99%
“…This conclusion is in agreement with Organization for Economic Cooperation and Development guidelines for acute toxicity tests with daphnids, which indicate that as little as 2 ml per organism is an acceptable test volume [27]. Moreover, Julli et al [9] reported no difference in survival or reproduction of the Sydney clone exposed in test volumes ranging between 40 and 200 ml and others have reported satisfactory results for tests conducted in 15‐ml volumes with the Sydney clone [10–11].…”
Section: Discussionsupporting
confidence: 82%
“…However, they noted that further improvements could be made with respect to diet and water in order to achieve consistently acceptable survival and reproductive performance. Moreover, subsequent studies conducted with this species used a variety of test and culture methods [10–13]. Consequently, our objective was to further evaluate the effects of container size and volume, diet, and dilution water on the survival and reproduction of the Sydney clone with the goal of validating existing procedures widely used in Canada and the United States.…”
Section: Introductionmentioning
confidence: 99%
“…comm.). With- (Anderson-Carnahan et al, 1995) and also reflect alteration in submerged aquatic out prior knowledge of the rankings based on the long-term data, the 10 wetlands were vegetation because chydorid cladocerans are reserves and stock routes, so it was not possible to obtain information on the frequency of algal blooms from land owners. Information on colour was not available owing to a mix-up with samples.…”
Section: Measurement and The Scoring Of Indicator Valuesmentioning
confidence: 99%